Persepsi Siswa Terhadap Penerapan Teori Humanistik Dalam Pembelajaran - Lailatul Ramadani; Rahayu Nugraheni; Ivo Sindia Nur Azizah (Journal of Humanities, Social Sciences, and Education, 2026)
The application of humanistic theory in learning is important because it can create a student-centered learning process while supporting the development of students’ cognitive, affective, and social aspects. However, in practice, teacher-centered learning is still found, limiting students’ opportunities to participate actively and develop their potential optimally. This study aims to describe students’ perceptions of the application of humanistic theory in learning. The study employed a qualitative approach with a descriptive research design. The research subjects consisted of 26 tenth-grade students at SMA Assubhan, Probolinggo Regency, selected using purposive sampling. Data were collected through observation, semi-structured interviews, and questionnaires, while data analysis employed the Miles, Huberman, and Saldaña model through data reduction, data display, and conclusion drawing. The results showed that students’ perceptions of the application of humanistic theory were categorized as good to very good. The teacher was perceived as capable of creating a comfortable learning environment, providing motivation, respecting students’ opinions, and encouraging active student participation in the learning process. The application of humanistic theory had a positive impact on students’ self-confidence, learning motivation, responsibility, and participation throughout the learning process.